Minimizing PVT-Variability by Exploiting the Zero Temperature Coefficient (ZTC) for Robust Delay Fault Testing - Jafarzadeh, Hanieh; Klemme, Florian; Reimer, Jan Dennis; Amrouch, Hussam; Hellebrand, Sybille; Wunderlich, Hans-Joachim (In: IEEE International Test Conference (ITC'24), San Diego, CA, USA, November 2024)

A Method for Identifying Use Cases in Data-Driven Product Management - Fichtler, Timm; Petzke, Lisa Irene; Grigoryan, Khoren; Koldewey, C.; Dumitrescu, Roman (Procedia CIRP)

Application Areas and Challenges of Data-Driven Product Management - Fichtler, Timm; Grigoryan, Khoren; Petzke, Lisa Irene; Koldewey, Christian; Dumitrescu, Roman (PACIS 2024 Proceedings)

Antecedents of Data-Driven Product Management – Data Taxonomy and Cluster & Software Categories - Fichtler, Timm; Petzke, Lisa Irene; Grigoryan, Khoren; Koldewey, C.; Dumitrescu, Roman (2024 IEEE International Conference on Technology Management, Operations and Decisions (ICTMOD))

Die Potentiale der Kreislaufwirtschaft für die Industrie - Rasor, Anja; Petzke, Lisa Irene; Vehmeyer, Julia; Koldewey, Christian; Dumitrescu, Roman (18. Symposium für Vorausschau und Technologieplanung)

Kunststoffrecycling im Lehrangebot der Universität Paderborn - Austermeier, Laura; Brüning, Florian; Schöppner, Volker; Schlüter, Alexander (Kunststoffland NRW Report)

Künstliche Intelligenz - Voraussetzungen für eine kompetente Nutzung und Bewertung - Herzig, Bardo (TELEVIZION)

"I'm actually going to go and change these passwords": Analyzing the Usability of Credential Audit Interfaces in Password Managers - Kablo, Emiram; Kader, Katharina; Arias Cabarcos, Patricia (Extended Abstracts of the CHI Conference on Human Factors in Computing Systems)

Mehrsprachigkeit als gemeinsame Haltung - Topalovic, Elvira (Beobachten im Deutschunterricht der Grundschule)

Energy Flexibility and Electrification of Industrial Process Heat: A Review - Knorr, Lukas; Schlosser, Florian; Divkovic, Denis; Buchenau, Nadja; Meschede, Henning

Approach for Optimal Selection of Innovative Actions for Residential Heating Systems - Polyvianchuk, Andrii; Petruk, Vasyl; Polyvianchuk, Natalia; Yurii, Kovalenko; Semenenko, Roman; Arsenyeva, Olga (Chemical Engineering Transactions)

Improvement in an Analytical Approach for Modeling the Melting Process in Single-Screw Extruders - Schöppner, Volker; Brüning, Florian; Knaup, Felix (Polymers)
Most single-screw extruders used in the plastics processing industry are plasticizing extruders, designed to melt solid pellets or powders within the screw channel during processing. In many cases, the efficiency of the melting process acts as the primary throughput-limiting factor. If the material melts too late in the process, it may not be sufficiently mixed, resulting in substandard product quality. Accurate prediction of the melting process is therefore essential for efficient and cost-effective machine design. A practical method for engineers is the modeling of the melting process using mathematical–physical models that can be solved without complex numerical methods. These models enable rapid calculations while still providing sufficient predictive accuracy. This study revisits the modified Tadmor model by Potente, which describes the melting process and predicts the delay-zone length, extending from the hopper front edge to the point of melt pool formation. Based on extensive experimental investigations, this model is adapted by redefining the flow temperatures at the phase boundary and accounting for surface porosity at the beginning of the melting zone. Additionally, the effect of variable solid bed dynamics on model accuracy is examined. Significant model improvements were achieved by accounting for reduced heat flow into the solid bed due to the porous surface structure in the solid conveying zone, along with a new assumption for the flow temperature at the phase boundary between the solid bed and melt film.
Keywords: delay zone; extrusion; melting modeling

Heat Transfer Enhancement in Compact Heat Exchangers with Channels of Different Geometries and Size - Arsenyeva, Olga; Kapustenko, Petro; Varbanov, Petar Sabev; Tovaznyanskyy, Leonid (Proceedings of the 27th Conference on Process Integration, Modelling and Optimisation for Energy Saving and Pollution Reduction, 25 – 28 August 2024, Xi’an, China)

Probing ferroelectric phase transitions in barium titanate single crystals via in-situ second harmonic generation microscopy - Kirbus, Benjamin; Seddon, Samuel D.; Kiseleva, Iuliia; Beyreuther, Elke; Rüsing, Michael; Eng, Lukas M. (Journal of Applied Physics)
Ferroelectric materials play a crucial role in a broad range of technologies due to their unique properties that are deeply connected to the pattern and behavior of their ferroelectric (FE) domains. Chief among them, barium titanate (BaTiO3; BTO) sees widespread applications such as in electronics but equally is a ferroelectric model system for fundamental research, e.g., to study the interplay of such FE domains, the domain walls (DWs), and their macroscopic properties, owed to BTO’s multiple and experimentally accessible phase transitions. Here, we employ Second Harmonic Generation Microscopy (SHGM) to in situ investigate the cubic-to-tetragonal (at ∼126°C) and the tetragonal-to-orthorhombic (at ∼5°C) phase transition in single-crystalline BTO via three-dimensional (3D) DW mapping. We demonstrate that SHGM imaging provides the direct visualization of FE domain switching as well as the domain dynamics in 3D, shedding light on the interplay of the domain structure and phase transition. These results allow us to extract the different transition temperatures locally, to unveil the hysteresis behavior, and to determine the type of phase transition at play (first/second order) from the recorded SHGM data. The capabilities of SHGM in uncovering these crucial phenomena can easily be applied to other ferroelectrics to provide new possibilities for in situ engineering of advanced ferroic devices.

Lattice Dynamics of LiNb(1–x)Ta(x)O3 Solid Solutions: Theory and Experiment - Bernhardt, Felix; Gharat, Soham; Kapp, Alexander; Pfeiffer, Florian; Buschbeck, Robin; Hempel, Franz; Pashkin, Oleksiy; Kehr, Susanne C.; Rüsing, Michael; Sanna, Simone; Eng, Lukas M. (physica status solidi (a))
Lithium niobate (LNO) and lithium tantalate (LTO) see widespread use in fundamental research and commercial technologies reaching from electronics over classical optics to integrated quantum communication. The mixed crystal system lithium niobate tantalate (LNT) allows for the dedicate engineering of material properties by combining the advantages of the two parental materials LNO and LTO. Vibrational spectroscopies such as Raman spectroscopy or (Fourier transform) infrared (IR) spectroscopy are vital techniques to provide detailed insight into the material properties, which is central to the analysis and optimization of devices. This work presents a joint experimental–theoretical approach allowing to unambiguously assign the spectral features in the LNT material family through both Raman and IR spectroscopy, as well as providing an in‐depth explanation for the observed scattering efficiencies based on first‐principles calculations. The phononic contribution to the static dielectric tensor is calculated from the experimental and theoretical data using the generalized Lyddane–Sachs–Teller relation and compared with the results of the first‐principles calculations.

Thermal conductivity in solid solutions of lithium niobate tantalate single crystals from 300 K up to 1300 K - Bashir, Umar; Rüsing, Michael; Klimm, Detlef; Blukis, Roberts; Koppitz, Boris; Eng, Lukas M.; Bickermann, Matthias; Ganschow, Steffen (Journal of Alloys and Compounds)
Lithium niobate tantalate (LiNb1−xTaxO3, LNT) solid solutions offer exciting new possibilities for applications ranging from optics, piezotronics, and electronics beyond the capabilities of the widely used singular compounds of lithium niobate (LiNbO3, LN) or lithium tantalate (LiTaO3, LT). Crystal growth of homogeneous LNT single crystals by the Czochralski method is still challenging. One key aspect of homogeneous growth is the accurate knowledge of thermal conductivity through the crystal boule during the growth, which is central to control the crystal growth. Therefore, the temperature dependent thermal conductivity of pure LN, LT, and LNT solid solutions, as well as of selected doped LN and LT crystals (Mg, Zn) was investigated across the temperature range from 300 to 1300 K. The results that span across the whole composition range can directly be applied for optimizing growth conditions of both LNT solid solutions as well as doped and undoped LN and LT crystals.

Two-dimensional electronic conductivity in insulating ferroelectrics: Peculiar properties of domain walls - Verhoff, Leonard M.; Pionteck, Mike N.; Rüsing, Michael; Fritze, Holger; Eng, Lukas M.; Sanna, Simone (Physical Review Research)
Ferroelectrics such as LiNbO3 (LN) are wide-band-gap insulators that may show a high local electric conductivity at the domain walls (DWs). The latter are interfaces separating regions of noncollinear polarization, which can be manipulated to build integrated nanoelectronic elements. In the present work, we model different DW types in LN from first principles. Our models reveal the DW morphology and shed light on their electronic properties: A strong band bending is predicted for charged DWs, leading to local metallicity. Defect trapping at the DW may further enhance the electric conductivity.

Toward the reproducible fabrication of conductive ferroelectric domain walls into lithium niobate bulk single crystals - Ratzenberger, Julius; Kiseleva, Iuliia; Koppitz, Boris; Beyreuther, Elke; Zahn, Manuel; Gössel, Joshua; Hegarty, Peter A.; Amber, Zeeshan H.; Rüsing, Michael; Eng, Lukas M. (Journal of Applied Physics)
Ferroelectric domain walls (DWs) are promising structures for assembling future nano-electronic circuit elements on a larger scale since reporting domain wall currents of up to 1 mA per single DW. One key requirement hereto is their reproducible manufacturing by gaining preparative control over domain size and domain wall conductivity (DWC). To date, most works on DWC have focused on exploring the fundamental electrical properties of individual DWs within single-shot experiments, with an emphasis on quantifying the origins of DWC. Very few reports exist when it comes to comparing the DWC properties between two separate DWs, and literally nothing exists where issues of reproducibility in DWC devices have been addressed. To fill this gap while facing the challenge of finding guidelines for achieving predictable DWC performance, we report on a procedure that allows us to reproducibly prepare single hexagonal domains of a predefined diameter into uniaxial ferroelectric lithium niobate single crystals of 200 and 300 μm thickness, respectively. We show that the domain diameter can be controlled with an uncertainty of a few percent. As-grown DWs are then subjected to a standard procedure of current-limited high-voltage DWC enhancement, and they repetitively reach a DWC increase of six orders of magnitude. While all resulting DWs show significantly enhanced DWC values, their individual current–voltage (I–V) characteristics exhibit different shapes, which can be explained by variations in their 3D real structure reflecting local heterogeneities by defects, DW pinning, and surface-near DW inclination.

Impact of ion exchange on vibrational modes in Rb-doped KTiOPO4: A Raman spectroscopy study on the interplay between ion exchange and polarization switching - Lee, Cherrie S. J.; Canalias, Carlota; Buschbeck, Robin; Koppitz, Boris; Hempel, Franz; Amber, Zeeshan; Eng, Lukas M.; Rüsing, Michael (Physical Review B)
Recently, ion exchange (IE) has been used to periodically modify the coercive field (Ec) of the crystal prior to periodic poling, to fabricate fine-pitch domain structures in Rb-doped KTiOPO4 (RKTP). Here, we use micro-Raman spectroscopy to understand the impact of IE on the vibrational modes related to the Rb/K lattice sites, TiO octahedra, and PO4 tetrahedra, which all form the basis of the RKTP crystal structure. We analyze the Raman spectra of three different RKTP samples: (1) a RKTP sample that shows a poled domain grating only, (2) a RKTP sample that has an Ec grating only, and (3) a RKTP sample that has both an Ec and a domain grating of the nominally same spacing. This allows us to determine the impact of IE on the vibrational modes of RKTP. We characterize the changes in the lower Raman peaks related to the alkali-metal ions, as well as observe lattice modifications induced by the incorporation of Rb+ that extend further into the crystal bulk than the expected IE depth. Moreover, the influence of IE on the domain walls is also manifested in their Raman peak shift. We discuss our results in terms of the deformation of the PO4and TiO groups. Our results highlight the intricate impact of IE on the crystal structure and how it facilitates periodic poling, paving the way for further development of the Ec-engineering technique.

Unveiling Electron‐Phonon and Electron‐Magnon Interactions in the Weak Itinerant Ferromagnet LaCo2P2 - Usachov, D. Yu.; Ali, K.; Poelchen, G.; Mende, M.; Schulz, S.; Peters, M.; Bokai, K.; Sklyadneva, I. Yu.; Stolyarov, V.; Chulkov, E. V.; Kliemt, K.; Paischer, S.; et al. (Advanced Physics Research)
Studying and understanding many‐body interactions, particularly electron‐boson interactions, is essential for a deeper elucidation of fundamental physical phenomena and the development of novel material functionalities. Here, this aspect is explored in the weak itinerant ferromagnet LaCo2P2 by means of momentum‐resolved photoelectron spectroscopy (ARPES) and first‐principles calculations. The detailed ARPES patterns enable to unveil bulk and surface bands, spin splittings due to Rashba and exchange interactions, as well as the evolution of bands with temperature, which altogether creates a solid foundation for theoretical studies. The latter has allowed to establish the impact of electron‐boson interactions on the electronic structure, that are reflected in its strong renormalization driven by electron‐magnon interaction and the emergence of distinctive kinks of surface and bulk electron bands due to significant electron‐phonon coupling. Our results highlight the distinct impact of electron‐boson interactions on the electronic structure, particularly on the itinerant d states. Similar electronic states are observed in the isostructural iron pnictides, where electron‐boson interactions play a crucial role in the emergence of superconductivity. It is believed that further studies of material systems involving both magnetically active d‐ and f‐sublattices will reveal more advanced phenomena in the bulk and at distinct surfaces, driven by a combination of factors including Rashba and Kondo effects, exchange magnetism, and electron‐boson interactions.